The efficacy of Transdiagnostic Cognitive Behavior therapy on reducing symptoms severity of Obsessive Compulsive Disorder with co-occurring anxiety and mood disorders - Saed, Omid; Masjedi, Abbas; Taremian, Farhad; Bakhtyari, Maryam; Morsali, Yosef (International Journal of Applied Behavioral Sciences, 2015)
Abstract Background: The aim of this study was to elucidate efficacy of transdiagnostic cognitive behavior therapy based on Unified Protocol (UP) for reducing symptoms severity of obsessive compulsive disorder (OCD) with co-occurring anxiety and unipolar mood disorders. Methods: From the thirty patients who participated to treatment, twenty four participants were randomly assigned to receive either immediate or delayed treatment. All participants were assessed using both clinician-rated and self-report measures. The immediate or intervention group were received 20 sessions taking one hour TCBT intervention based on UP but delayed group did not receive any intervention. After gathering the data from two groups, the UP was implemented for delayed or control group. Three regular assessment administrated that consisted of pretest, posttest, and a month follow-up (FU). Results: The UP afforded a very strong effect on diagnostic severity, obsessive compulsive frequency of symptoms, dimensions and total functioning for principal diagnoses from pretreatment to FU. Effect size statistics for assessing treatment gains showed large effects (of 1.49 to 2.64) for heterogonous comorbid disorders that was retained on follow-up. The differences in the proportion of individual achieving responders and high end-state function (HESF) between comorbid diagnoses at post treatment and FU were not statistically significant. Conclusion: Results from this study provide additional evidence for the efficacy of the UP in the treatment of OCD with co-occurring anxiety and unipolar depressive disorders, and provide additional support for a transdiagnostic approach to the treatment of emotional disorders.